Optimising Femtocell Placement in an Interference Limited Network: Theory and Simulation - Siyi Wang; Weisi Guo; O'Farrell, T. (2012 IEEE Vehicular Technology Conference (VTC Fall), 2012)
The purpose of this paper is to show that the indoor downlink capacity and energy efficiency can be significantly improved by optimising the indoor location of femtocell. This body of investigation is done in the presence of outdoor interference and the simulation results are backed up by a novel theoretical framework employing convex optimisation. Moreover, this optimisation problem has been demonstrated to be meaningful in the context of considering capacity saturation of realistic modulation and coding schemes. The results yield insight into the relationship between the outdoor and indoor aspects of the cellular network, as well as the propagation parameters. The paper shows that a mean capacity improvement of up to 20% can be made with optimal placement, which translates to an operational energy reduction of 8%. Moreover, it has been shown that the optimisation does not significantly degrade the performance of outdoor network. The global impact of this work is that 1.6 TWh can be saved globally, which amounts to the energy produced by two 1000 MW power plants.